The Influence Of Product Attributes And Word Of Mouth Communication On Purchasing Decisions For Xl Axiata Prepaid Cards - St Arwini Alwy; Otto R. Payangan; Fahrina Mustafa (SEIKO : Journal of Management & Business, 2023)
The purpose of this study was to determine how the influence of product attribute variables and word-of-mouth communication, as well as variables that have a dominant influence between the two variables on purchasing decisions for XL Axiata prepaid cards. In this study, researchers used a purposive sampling technique and primary data obtained by distributing questionnaires to 100 students of the faculty of economics and business, Hasanuddin University, who used XL Axiata prepaid cards. The analysis method used is multiple linear regression analysis with several test tools, namely validity test, reliability test, F hypothesis test and t hypothesis using the SPSS program. The results showed that based on the simultaneous test, the product attribute variables and word-of-mouth communication significantly affected purchasing decisions. However, the product attribute variable partially has a significant effect, while the word-of-mouth communication variable has no significant effect on purchasing decisions. Keywords: Product attributes, Word-of-mouth communication, purchasing decisions